Determinants of Foreign Currency Borrowing in the New Member States of the EU - Rosenberg, Christoph (IMF Working Papers; Working Paper, 2008)
The paper investigates the determinants of foreign currency borrowing by the private sector in the new member states of the European Union. We find that striking differences in patterns of foreign currency borrowing between countries are explained by the loan-to-deposit ratios, openness, and the interest rate differential. Joining the EU appears to have played an important role, by providing direct access to foreign funding, offering hedging opportunities through greater openness, lending credibility to exchange rate regimes, and raising expectations of imminent euro adoption. The empirical evidence suggests that regulatory policies to slow foreign currency borrowing have had only limited success.